Statins in Secondary Prevention of Atrial Fibrillation - V. I. Podzolkov; A. I. Tarzimanova; R. G. Gataulin (Рациональная фармакотерапия в кардиологии)
Aim. To study the effect of atorvastatin on the progression of the arrhythmia in hypertensive patients with paroxysmal atrial fibrillation (AF) in the longterm follow-up.Material and methods. Patients with paroxysmal AF (n=65) were included into the study. The patients were divided into two groups depending on the level of lipid metabolism: group I (n=33) received atorvastatin (10-40 mg/day), and control group II (n=32) did not take statins. The duration of follow-up was 4 years. The evolution of the AF clinical course was evaluated by the number of arrhythmia episodes for 3 months. Increase in the frequency of paroxysms of AF over the past 3 months, the appearance of the long-standing persistent AF or permanent AF considered as the arrhythmia progression.Results. The increase in rate and duration of AF episodes was found in 14 (42%) patients of group I and in 13 (41%) patients of group II. Progression of AF was observed with equal frequency in groups I and II. The average value of arrhythmia progression was 10.5% per year in patients of group I and 10.3% in group II. Significant differences between groups in the progression of AF were not found (p=0.2).Conclusion. Atorvastatin in hypertensive patients with paroxysmal AF did not lead to a change in rate and duration of arrhythmia paroxysms. The average value of paroxysmal AF progression was comparable regardless of atorvastatin use.